Pengaruh Tingkat Konsumsi Zat Gizi Makro, Pengetahuan tentang Gizi dan Body Image terhadap IMT Remaja Putri di MAN 2 Manggarai - Salwa Shalimar; Intje Picauly; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Adolescents often experience problems such as malnutrition, overweight, and micronutrient deficiencies with anemia. BMI is a method for determining the nutritional status of adolescents. An individual's nutritional status can be influenced by both direct and indirect factors. Macronutrient consumption levels, knowledge of nutrition, and body imageare related factors that affect BMI. This research aims to determine the influence of macronutrient consumption levels, nutrition knowledge, and body imageon the BMI of female adolescents at MAN 2 Manggarai. This study utilized an quantitativewith a cross-sectional design, employing purposive sampling techniques on 76 female students. The results of the study indicate a influence between fat consumption levels (p=0.022), nutrition knowledge (p=0.001), body image(p=0.044), and BMI of female adolescents at MAN 2 Manggarai. Meanwhile, protein consumption level (p=0.145) and carbohydrate consumption level (p=0.188) show no influence on the BMI of female adolescents. It is recommended to provide nutrition education, monitor nutritional status at schools, and encourage adolescents to pay more attention to their dietary intake.